Ultrasonic Partial Discharge Monitoring Method On Instrument Transformers - Kartalovic, Nenad M; Ilić, Nikola; Milošević, Ana; Teslić, Dragan; Cakić, Nikola N.; Milosavljević, Srđan (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
Sonic and ultrasonic partial discharge monitoring have been applied since the early days of these phenomena monitoring. Modern measurement and partial discharge acoustic (ultrasonic and sonic) monitoring method has been rapidly evolving as a result of new electronic component design, information technology and updated software solutions as well as the development of knowledge in the partial discharge diagnosis. Electrical discharges in the insulation system generate voltage-current pulses in the network and ultrasonic waves that propagate through the insulation system and structure. Amplitude-phase-frequency analysis of these signals reveals information about the intensity, type and location of partial discharges. The paper discusses the possibility of ultrasonic method selectivity improvement and the increase of diagnosis reliability in the field. Measurements were performed in the laboratory and in the field while a number of transformers were analysed for dissolved gases in the oil. A comparative review of methods for the partial discharge detection is also presented in this paper.